(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The main objective of this research is to find out alternative materials for concrete to meet the demands of coarse aggregate for the upcoming years, to provide adequate strength at minimum cost, to make the eco-friendly structures.Â Use of ferro slag a waste industrial by-product of iron and steel production provides great opportunity to utilize it as an alternative to normally available aggregates (coarse). In this research, ferro slag is used and M60 grade concrete ofÂ W/C ratio 0.28 was used respectively for the replacement of 0 to 100% coarse aggregate by ferro slag aggregate for find out the optimum ratio of steel slag. In this study, a mix ratio of 1: 1.2: 2.4 is used in conventional mix. Initial optimization ofÂ ferro slag aggregate for replacing the natural coarse aggregate was find with 7and 28 days strength. Test on compressive strength and non-destructive test at 7 and 28 days were conducted. It was concluded that possible optimum replacement of slag material was found to be 40%. Split Tensile Strength and Flexural Strength and durability characteristics were carried out for conventional and optimum concrete mix to study the properties of concrete with ferro slag.